Three-Dimensional Printing Technology in Orthodontics for Dental Models: A Systematic Review - Ioannis A. Tsolakis; Sotiria Gizani; Nearchos Panayi; Georgios Antonopoulos; Apostolos I. Tsolakis (MDPI AG, 2022)
Background: Three-dimensional printing technology is an additive manufacturing technology that is used to reconstruct 3D objects. In the last decade, it has been rapidly involved in dentistry and in orthodontics. This article aims to review the literature and present the accuracy of different 3D printer types and any factors that could affect the 3D printing of dental models in the orthodontic field. Methods: The search strategy of this systematic review included keywords in combination with MeSH terms in Medline, Scopus, and Cochrane Library until June 2022 and only in English. Results: Eleven articles were selected for our study. All the articles were in vitro prospective studies, and they presented a low risk of bias. The results suggested that the accuracy of a printed dental cast can be affected by the different types of 3D technologies, the dental cast's base design, and the printing materials. The accuracy appears to not be affected by the layer height and the position of the model on the building template. Conclusions: According to this systematic review, all different types of 3D technology can produce clinically accepted results for orthodontic purposes. There is a need for more studies to clarify the accuracy and added value of 3D printing technology in orthodontics.